AKTIVITAS KOMUNIKASI PADA PAGELARAN SENI REAK DALAM MERAYAKAN PANEN PADI - Olih Solihin; Ariq Asykarulloh; Yuni Mogot; Yasundari Yasundari (Universitas Pakuan, 2022)
This study aims to analyze communication activities in the Reak Juarta Putra art performance as a form of gratitude for the abundance of rice yields by the people of Ciguruwik Village, Cinunuk Village, Bandung Regency, West Java. Researchers used a qualitative approach with the ethnographic method of communication. The results of this study show: 1) the situation of the ritual communication of the Juarta Putra reak art performance where the implementation took place in the yard of the Traditional Stakeholders' House in Ciguruwik Village; 2). The communicative event of the Juarta Putra reak art performance ritual took place with tawasulan, traditional rituals, opening by traditional stakeholders, art performances, and closing rituals by traditional stakeholders; 3). Communicative acts of the Juarta Putra reak art performance ritual, namely there are symbols of messages and philosophies from ancestors that are believed by the people of Kampung Ciguruwik which exist in the meaning of harvesting rice, burning incense and offerings. The conclusion of the ritual communication activity for the Juarta Putra reak art performance is an activity in communication activities that is routine every year, while the ritual for the Juarta Putra reak art performance is a series of unique events and has characteristics that distinguish it from other traditions.